Identifikasi Ukuran Tubuh dan Bentuk Tubuh Sapi Bali di Beberapa Pusat Pembibitan Melalui Pendekatan Analisis Komponen Utama - Hikmawaty, Hikmawaty; Gunawan, A.; Noor, R. R.; Jakaria, Jakaria (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2014)
Bali cattle is indigenous livestock genetic resources which have distinctive features and ability to grow well in a variety of environments in Indonesia. The aim of this study was to determine the phenotypic profile of Bali cattle in some breeding centers which represented by BPTU Pulukan Bali, VBC Kab. Barru South Sulawesi and BPTHMT Serading NTB. Data were analyzed by using Principal Component Analysis (SAS) to determine the size identifier which was influenced by the environmental factors and genetic factors form  the basic information on the characteristics of Bali cattle. The parameters such as dimensions and body weight of Bali cattle due to the possibility of differences in genetic potential, location of origin, implementation of the mating system and environmental management including maintenance were observed. The result showed Bali cattle body size on BPTHMT Serading NTB  were smaller (P <0.5) compared to the body size of Bali cattle in BPTU Pulukan Bali and VBC Kab. Barru South Sulawesi while Bali cattle in BPTU Pulukan Bali and VBC Kab. Barru South Sulawesi were relatively similar. Chest girth measured on the body has the highest correlation with body weight in Bali cattle both in males and females in different breeding centers.The size score and the shape between Bali cattle breeding centers in the male and female Bali cattle showed its own characteristics due to their respective locations. Identifier the size of Bali cattle at NTB Serading BPTMHT showed relatively smaller than Bali Cattle in BPTU Pulukan Bali and VBC Kab. Barru SouthSulawesi. Identifier the same shape among all three populations showed the breeding centers have the samecharacteristic genetically.